Multipolar electrostatics for hairpin and pseudoknots in RNA: Improving the accuracy of force field potential energy function. Issue 11 (15th February 2021) - Yuan, Yongna; Fu, Shaowei; Huo, Dongxu; Su, Wei; Zhang, Ruisheng; Wei, Jiaxuan
Abstract: Molecular dynamics (MD) simulations that rely on force field methods has been widely used to explore the structure and function of RNAs. However, the current commonly used force fields are limited by the electrostatic description offered by atomic charge, dipole and at most quadrupole moments, failing to capture the anisotropic picture of electronic features. Actually, the distribution of electrons around atomic nuclei is not spherically symmetric but is geometry dependent. A multipolar electrostatic model based on high rank multipole moments is described in this work, which allows us to combine polarizability and anisotropy of electron density. RNA secondary structure was taken as a research system, and its substructures including stem, loops (hairpin loop, bulge loop, internal loop, and multi‐branch loop), and pseudoknots (H‐type and K‐type) were investigated, respectively, as well as the hairpin. First, the atom–atom electrostatic properties derived from one chain of a duplex RNA 2MVY in our previous work (Ref. 58) were measured by the pilot RNA systems of hairpin, hairpin loop, stem, and H‐type pseudoknot, respectively. The prediction results were not satisfactory. Consequently, to obtain a general set of electrostatic parameters for RNA force fields, the convergence behavior of the atom–atom electrostatic interactions in the pilot RNA systems was explored using high rank atomic multipole moments. The pilot RNA systems were cut into four types of different‐sized molecular fragments, and the single nucleotide fragment and nucleotide‐paired fragment proved to be the most reasonable systems for base‐unpairing regions and base‐pairing regions to investigate the convergence behavior of all types of atom–atom electrostatic interactions, respectively. Transferability of the electrostatic properties drawn from the pilot RNA systems to the corresponding test systems was also investigated. Furthermore, the convergence behavior of atomic electrostatic interactions in other substructures including bulge loop, internal loop, multi‐branch loop, and K‐type pseudoknot was expected to be modeled via the hairpin. Abstract :